Severity Grading, Management, Outcome and Epidemiological Profiling of Snakebite Victims in Tertiary Care Hospital in South India: 5 Years Retrospective Study - Smriti Sinha1, Sathyajith Karanth2, Avinash Kumar3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: We conducted this study to do epidemiological and clinical profiling of the patients with snake bite in a tertiary care referral centre, situated in suburban area of Dakshin Kannada district, Karnataka, south India.Materials and Method: This retrospective, record based study was done by analysing medical records of all the patients of snake bite admitted over 5years from June 2015 to July 2019. It included demographic details and clinical profiling. Based on presenting complaint, clinical sign/symptoms and laboratory reports snake envenomation patients were divided into neurotoxic and hemotoxic group. The severity grading, amount of ASV used and outcome assessed in both the groups.Results: Total 108 patient records were analysed, maximum of which were males (64.8%) in age group of 15-30 years (46.2%). In majority of the cases the species of snake was not identified (67.5%). Dry bites were reported in 40.7% cases, among envenomated cases, 68.7% presented with hemotoxic syndrome, 29.7% with neurotoxic syndrome and 0.9% had both the features. In all envenomated patients with increasing bite to needle time, the grade of severity, amount of used ASV, duration of hospital stay and complications were found to increase.Conclusion: Snake bite is a neglected life threatening condition, which is a preventable disease. Tourniquet is still very commonly used first aid technique, which can be deleterious. The lack of education and awareness about snake bite management was evident and active mass education is clearly needed.